The Impact of Board Diversity and Gender Composition on Corporate Social Responsibility and Firm Reputation - Bear, Stephen; Rahman, Noushi; Post, Corinne (2010)
This article explores how the diversity of board resources and the number of women on boards affect firms’ corporate social responsibility (CSR) ratings, and how, in turn, CSR influences corporate reputation. In addition, this article examines whether CSR ratings mediate the relationships among board resource diversity, gender composition, and corporate reputation. The OLS regression results using lagged data for independent and control variables were statistically significant for the gender composition hypotheses, but not for the resource diversity-based hypotheses. CSR ratings had a positive impact on reputation and mediated the relationship between the number of women on the board and corporate reputation.
Keywords: gender composition; boards of directors; Board diversity; Corporate Social Responsibility; Corporate Reputation